2010
DOI: 10.1080/15434303.2010.510899
|View full text |Cite
|
Sign up to set email alerts
|

Examination Preparation or Effective Teaching: Conflicting Priorities in the Implementation of a Pedagogic Innovation

Abstract: Communicative and task-based teaching hold central places in contemporary language pedagogy, yet their feasibility as pedagogic innovations in Chinese contexts remains open to question. Examinations are generally perceived as a particular factor militating against the implementation of communicative approaches. This study uses four case studies of teachers in two primary schools in China to provide in-depth empirical data, drawn from 55 lesson observations and a series of related interviews, focusing on the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…However, preparing students for examinations was strongly related to teachers' self-reported classroom practices of controlling students and testing them. Similarly, Deng and Carless (2010) reported that the presence of high-stakes external examinations impeded the use of a task-based, communicative language pedagogy in early primary school teaching.…”
Section: Conceptions Of Assessmentmentioning
confidence: 97%
“…However, preparing students for examinations was strongly related to teachers' self-reported classroom practices of controlling students and testing them. Similarly, Deng and Carless (2010) reported that the presence of high-stakes external examinations impeded the use of a task-based, communicative language pedagogy in early primary school teaching.…”
Section: Conceptions Of Assessmentmentioning
confidence: 97%
“…The identified minimum recommendation, in many cases, exceeds those commonly used for admissions (e.g., IELTS 6.0). The use of oral tasks should, therefore, be carefully considered by instructors of undergraduate courses to ensure that all students have the same opportunity to demonstrate learning and that assessment methods match pedagogical requirements (Deng and Carless 2010).…”
Section: Entrance Requirements and Band Descriptorsmentioning
confidence: 99%
“…For example, Deng and Carless (2010) [12] have observed contradictions in language teaching and examinations amongst the language teachers in China. While the impetus leans towards a more communicative language teaching (CLT) curriculum and task-based language teaching (TBLT) in English, they tend to react to these calls for changes according to their personal philosophies.…”
Section: Tension In Assessment Practicementioning
confidence: 99%